Changes in Dry Matter, Oleoresin and Bioactive Components during Ripening of Different Chilli Pepper Cultivars of Nepal - Subedi, U.; Karki, R.; Ojha, P.; Shrestha, S.L. (Nepalese Horticulture, 2018)
Abstract available with the full text.